2018
DOI: 10.1186/s40557-018-0213-4
|View full text |Cite
|
Sign up to set email alerts
|

Sick at work: prevalence and determinants among healthcare workers, western Ethiopia: an institution based cross-sectional study

Abstract: BackgroundGoing to work despite feeling sick also known as sickness presenteeism is one of the emerging global occupational health challenges. Sickness presenteeism negatively affects both health of work forces and productivity of organizations in general. However, there is insufficient research exploring this situation in majority of the Sub-Saharan African countries, including Ethiopia. Thus this study intended to investigate the prevalence and determinant factors of sickness presenteeism among health care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 30 publications
1
29
2
8
Order By: Relevance
“…Similar results were obtained by Mekonnen et al in whose study of healthcare workers it was shown that pressure from the supervisor and a shortage of personnel are significant predictors of presenteeism [19].…”
Section: Introductionsupporting
confidence: 88%
“…Similar results were obtained by Mekonnen et al in whose study of healthcare workers it was shown that pressure from the supervisor and a shortage of personnel are significant predictors of presenteeism [19].…”
Section: Introductionsupporting
confidence: 88%
“…Nor is there a perfect consensus with respect to the population in which to estimate SP or, to put it another way, the denominator that should be used when estimating frequency measures. There are studies in which the population considered is all workers and others, noting that to be presenteeist the worker first must meet the condition of being “sick,” exclude “healthy” workers (considered “not at risk”) …”
Section: Resultsmentioning
confidence: 99%
“…Second, it is likely that low absenteeism can be an indicator of presenteeism among the medical staff, which is the phenomenon in which an employee goes to work despite feeling so ill that sick absenteeism would have been appropriate 41 . Even though sickness presenteeism is common in all working populations, studies have shown that its prevalence increases in the care sector and among healthcare workers likely because the service they provide is customer contact in its nature and compels to the high physical presence requirement 42,43 . Therefore, the small excess of absenteeism of medical doctors may be because they are educated workers and may be more likely to have high responsibility assignments and to have high job attendance requirements.…”
Section: Discussionmentioning
confidence: 99%
“…41 Even though sickness presenteeism is common in all working populations, studies have shown that its prevalence increases in the care sector and among healthcare workers likely because the service they provide is customer contact in its nature and compels to the high physical presence requirement. 42,43 Therefore, the small excess of absenteeism of medical doctors may be because they are educated workers and may be more likely to have high responsibility assignments and to have high job attendance requirements. These suggestions were consistent with the findings of other studies, [44][45][46] which demonstrated that the level of education of participants and responsibility assignments for relatively more educated participants were significantly associated with sickness presenteeism.…”
Section: F I G U R E 2 Comparison Of Excess Of Absenteeism Between Momentioning
confidence: 99%